Pengaruh Layanan Bimbingan Kelompok Teknik Konseling Behavioral Terhadap Peningkatan Kesehatan Mental - Suriawati Zega; Famahato Lase; Elizama Zebua; Hosianna Redearni Damanik (Departement of Mathematics Education, 2024)
Problems, development and improvement of mental health can be done with group guidance services (BKp) behavioral counseling techniques. The aim of the research is to reveal the influence of BKp services (X1) and behavioral counseling techniques (X2) on improving mental health (Y), using associative strategy quantitative methods. The research location was SMP Negeri 6 Idanogawo, the research population was all class VIII students and the sample was taken purposively as many as 32 people. The data collection instrument was a closed questionnaire which was distributed to a number of respondents. Data were analyzed using multiple linear regression analysis to answer research questions according to the proposed hypothesis. The research results concluded that BKp services (X1) partially had a significant effect on improving mental health (Y). The regression coefficient value of the BKp service variable is negative, namely 5.279 and every increase in BKp services by 1.00% will be followed by an increase in mental health by 5.279%. Behavioral counseling techniques (X2) partially have a significant effect on improving mental health (Y). The regression coefficient value for behavioral counseling techniques is positive, namely 6.098 and every 1.00% increase in behavioral counseling techniques will be followed by an increase in mental health of 6.098%. Variables X1 and X2 together have a significant effect on variable Y and every increase in X1 and The contribution of the influence of variables X1 and X2 to variable Y is 91.80%, while the remaining 8.2% is influenced by other variables that have not been studied. It is recommended for school counselors to provide BKp services with behavioral counseling techniques to handle, develop and improve students' mental health.